Antiglioma oncolytic virotherapy: unattainable goal or a success story in the making?. (July 2013) - Dey, Mahua; Auffinger, Brenda; Lesniak, Maciej S; Ahmed, Atique U
Initial observations from as early as the mid-1800s suggested that patients suffering from hematological malignancies would transiently go into remission upon naturally contracting viral infections laid the foundation for the oncolytic virotherapy research field. Since then, research focusing on anticancer oncolytic virotherapy has rapidly evolved. Today, oncolytic viral vectors have been engineered to stimulate and manipulate the host immune system, selectively targeting tumor tissues while sparing non-neoplastic cells. Glioblastoma multiforme, the most common adult primary brain tumor, has a disasterous history. It is one of the most deadly cancers known to humankind. Over the last century our understanding of this disease has grown exponentially. However, the median survival of patients suffering from this disease has only been extended by a few months. Even with the best, most aggressive modern therapeutic approaches available, malignant gliomas are still virtually 100% fatal. Motivated by the desperate need to find effective treatment strategies, more investments have been applied to oncolytic virotherapy preclinical and clinical studies. In this review we will discuss the antiglioma oncolytic virotherapy research field. We will survey its history and the principles laid down to serve as basis for preclinical works. We will also debate the variety of viral vectors used, their clinical applications, the lessons learned from clinical trials and possible future directions.